2016
DOI: 10.1073/pnas.1602319113
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged activation of innate antiviral gene signature after childbirth is determined byIFNL3genotype

Abstract: Maternal innate and adaptive immune responses are modulated during pregnancy to concurrently defend against infection and tolerate the semiallogeneic fetus. The restoration of these systems after childbirth is poorly understood. We reasoned that enhanced innate immune activation may extend beyond gestation while adaptive immunity recovers. To test this hypothesis, the transcriptional profiles of total peripheral blood mononuclear cells following delivery in healthy women were compared with those of nonpregnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…This minor allele genotype of rs12979860 (TT) has also been associated with a higher and prolonged ISG expression in HCV infection (79,80,87,90,103,111). Interestingly, the same SNP of the IFNL3 gene is associated with a higher ISG expression in mothers after childbirth, suggesting that postpartum the normalization of physiological control of IFN signaling depends on the IFNL3 genotype (112). Although the rs12979860 SNPs have been specifically associated with IFNL3/ L4 expression, these SNPs might also affect the expression of the other IFN-λ genes (80,87,113).…”
Section: Impact Of Snpsmentioning
confidence: 99%
“…This minor allele genotype of rs12979860 (TT) has also been associated with a higher and prolonged ISG expression in HCV infection (79,80,87,90,103,111). Interestingly, the same SNP of the IFNL3 gene is associated with a higher ISG expression in mothers after childbirth, suggesting that postpartum the normalization of physiological control of IFN signaling depends on the IFNL3 genotype (112). Although the rs12979860 SNPs have been specifically associated with IFNL3/ L4 expression, these SNPs might also affect the expression of the other IFN-λ genes (80,87,113).…”
Section: Impact Of Snpsmentioning
confidence: 99%
“…It is postulated that the innate immune system will play a significant role against pathogens, while the adaptive immune responses are dampened by increased Tregs activity (89, 90). Another recent study showed that the expression of innate immunity genes is enriched in postpartum women compared to control (91). Interestingly, ISGs level in women of the CT or TT IFN-λ3 rs12979860 genotype remained elevated as late as 24 weeks after childbirth, while women with the CC IFN-λ3 genotype were comparable to non-pregnant controls (91).…”
Section: Type III Ifns and Hcv-specific Immunity During Pregnancymentioning
confidence: 99%
“…Another recent study showed that the expression of innate immunity genes is enriched in postpartum women compared to control (91). Interestingly, ISGs level in women of the CT or TT IFN-λ3 rs12979860 genotype remained elevated as late as 24 weeks after childbirth, while women with the CC IFN-λ3 genotype were comparable to non-pregnant controls (91). This reflects what was observed in the context of acute HCV where individuals with non-favorable CT or TT IFN-λ3 genotype had a higher baseline ISG expression in the liver.…”
Section: Type III Ifns and Hcv-specific Immunity During Pregnancymentioning
confidence: 99%
“…Growing literature demonstrates genetic associations between rs368234815 or its linked variants with other clinical phenotypes, such as relapse on DAA treatment of HCV (12), liver fibrosis (13, 14), hepatic metallothionein expression (15), post-partum immune activation (16, 17), risk of mucinous ovarian cancer (18), etc. Although other, invariantly expressed type-III IFNs might be also important for these phenotypes, only IFN-λ4 is directly and most dramatically affected by the associated variant, rs368234815, that either creates or eliminates IFN-λ4.…”
Section: Introductionmentioning
confidence: 99%